Cover Image. (19th June 2019) - Fu, Xing; Li, Hong‐Nan; Wang, Jia
Abstract : The cover image is based on the Research Article Failure analysis of a transmission tower subjected to combined wind and rainfall excitations by Xing Fu et al., https://doi.org/10.1002/tal.1615 .